Efektivitas Penanganan Kasus Kekerasan Terhadap Anak Oleh Dinas Sosial Pemberdayaan Perempuan dan Perlindungan Anak di Kota Probolinggo - Astuti Nawangsih, Veronica Sri; Yunus, Eko Yudianto; Astono, Tidar (Jurnal Sosial Humaniora Sigli, 2025)
Handling cases of violence against children is a crucial part of efforts to protect children's rights and ensure their sense of safety. This study aims to analyze the effectiveness of handling child abuse cases by the Department of Social Affairs, Women Empowerment, and Child Protection (Dinsos P3A) of Probolinggo City. This research employs a qualitative descriptive approach with data collected through interviews, observations, and documentation. The findings indicate that Dinsos P3A has implemented several measures such as psychological assistance, legal aid, and cross-sectoral coordination with the police and child protection institutions. However, the effectiveness of these efforts faces several obstacles, including limited human resources, inadequate supporting facilities, and low public awareness in reporting cases. Nevertheless, the preventive and curative actions taken have shown positive progress in reducing the number of child abuse cases in Probolinggo City. This study recommends strengthening cross-sectoral collaboration and enhancing the capacity of field officers as strategies to improve the effectiveness of future case handling.Keywords: Effectiveness, Child Abuse, Child Protection, Dinsos P3A, Probolinggo City